Clinical and laboratory profile of children with dengue fever admitted at a tertiary care hospital in Mangalore, Karnataka, India: a retrospective study - M., Tejaswini; S., Sahana K.; Saldanha, Prakash R. M. (International Journal of Contemporary Pediatrics, 2020)
Background: Dengue fever caused by dengue virus is a self-limiting acute febrile illness transmitted by Aedes aegypti, a daytime biting mosquito. Dengue virus belongs to family of Flaviviridae and there are 4 serotypes. A fifth serotype DENV-5 was isolated in 2013 which was said to cause mild form of the disease. In 2019 total numbers of dengue cases are 10,524 in Karnataka which is 138% increase over 2018 (4,427 cases). Methods: A retrospective conducted in Yenepoya Medical College hospital from January 2017 to July 2019 for a period of 2½ years. Medical records of children who were diagnosed with dengue fever were retrieved and analyzed. Clinical and laboratory findings were noted down. Clinical course and outcome were noted down from the case sheet and cases were classified as per WHO 2011 classification. Results: 97 children diagnosed with dengue fever were included in the study. Common age group was 5-15 years. 49.5% had dengue fever, 40.2% had dengue haemorrhagic fever (DHF) and 10.3% had expanded dengue syndrome. Fever was the main complaint. Children with dengue fever presented with vomiting, abdominal pain, myalgia, arthralgia in descending order of frequency. Children with DHF, petechiae were seen in 38% patients. Among bleeding manifestations, epistaxis was more common. Children with expanded dengue syndrome had atypical manifestations. Conclusions: Dengue fever like any other viral illness, presents with prodromal symptoms which should be picked up at the earliest with high index of suspicion in children coming from endemic area. Identification of atypical manifestations and co-infections at the earliest and prompt treatment avoids serious life-threatening complications.